INTERPRETATION OF BAKUREH PROJECT ARCHIVES DAUR SUBUR PROGRAM #4 GUBUAK KOPI COMMUNITY INTO COLLAGE WORKS - Jonneva, Volta Ahmad; Zam, Riswel (Journal of Learning on History and Social Sciences, 2024)
Collage work is the art of cutting and sticking on a flat surface, in the form of two-dimensional works of art that use various materials as a medium to create an artistic composition. In this case, the collage work comes from a program initiated by the Komunitas Gubuak Kopi entitled Daur Subur, which is an art platform as a study of the culture that develops in agricultural communities in Solok City, West Sumatra. In the Daur Subur program there is an archive of documentation collected during activities, which have been running from 2017 until now. In 2018 the Daur Subur#4 program launched a special theme entitled "Bakureh." This collection of archives on the theme "Bakureh" was then made into a collage work carried out through an interpretation process. The method used in producing this work refers to Alma Hawkins which consists of; exploration, improvisation, and shaping. This method will be used in every process of creating a collage work, from collecting all the curated archives to finishing the work. From this process eight works were created with the title; Proses Bakureh, Dapur dan Tungku, Julo-Julo, Pesta Warga, Rumah dan Istirahatnya, Bararak Menuju Sore, Gotong Royong, dan Suasana Dapur dan kepala yang Sibuk. After the collage work is created, the work is then presented by hanging it on a sketchpad and arranging it according to the concept and title of each work. The publication was carried out in the form of a solo exhibition which was given the same title as the Daur Subur program, namely “Potongan di Meja Dapur Komunal”